Regional Chemotherapy of the Lung: Transpulmonary Chemoembolization in Malignant Lung Tumors - Vogl, Thomas J.; Shafinaderi, Mohammad; Zangos, Stefan; Lindemayr, Sebastian; Vatankhah, Khashayar (Seminars in Interventional Radiology, 2013)
Standard treatment options in patients with lung cancer and pulmonary metastases are surgery, radiotherapy, chemotherapy, and immunotherapy. For reducing clinical complications of surgery and achieving a better local response, transpulmonary chemoembolization of the lungs is a possible interventional technique in which anticancer drugs are administered directly into a tumor through its feeding vessels followed by occlusive agents that are injected through the delivery catheter for blocking the vessel. This allows a longer contact period in the tumor with a higher cytostatic drug concentration. The technique is safe and results present promising local response rates, but the influence on survival is still questionable. This article describes the current role of intravascular therapies in the treatment of pulmonary malignancies.
Keywords: primary lung malignancy; secondary lung malignancy; transpulmonary chemoembolization (TPCE); isolated lung perfusion; bronchial artery infusion; lung suffusion; interventional radiology